Efeito de diferentes protocolos de limpeza do espaço do canal radicular preparado para o pino sobre a resistência ao deslocamento de pinos de fibra de vidro cimentados com cimento autoadesivo : estudo in vitro - Ouriques, Maurício Cernicchiaro (2022)
Fiberglass posts (FGP) are an alternative to metal posts for the restoration of endodontically treated teeth due to mechanical and aesthetic properties. However, FGP frequently fail because of debonding. The purpose of this study was to evaluate the influence of different irrigation protocols for the post space cleaning on the bond strength of FGP cemented with Relyx U-200™. The sample comprised of 60 single-rooted, with a single canal, extracted human teeth. After the root canal treatment, post spaces were prepared and the specimens divided into 6 groups (n=10) according to the irrigation protocol: G1 – irrigation with 2.5% NaOCl for 1 minute (flow of 5 mL/min)+ 17% EDTA for 3 minutes (under stirring with hand file) + 2.5% NaOCl for 1 minute (flow of 5 mL/min); G2 – irrigation with 2.5% NaOCl for 1 minute (flow of 5 mL/min) + EDTA 17% in 3 cycles of passive ultrasonic irrigation (PUI), for 20 seconds each, renewing the solution every cycle + 2.5% NaOCl for 1 minute (flow of 5 mL/min); G3 – irrigation with 2% chlorhexidine (CHX); G4 – irrigation with 2% CHX + PUI; G5 – irrigation with 0.9% saline; G6 – irrigation with 0.9% saline + PUI. The FGP were then cemented with the self-adhesive cement. Cross sections of the thirds were obtained and submitted to the push-out test. The data obtained were evaluated by using One-way ANOVA and Tukey’s post hoc test for comparison among different groups, and t Test for dependent samples to compare the different thirds in the same group (= .05). G2 (180.90 N; DP±19.72) and G5 (177.10 N; DP±70.82) presented the highest values of bond strength, statistically differing from G3 (93.18 N; DP±39.13) and G4 (99.45 N; DP±44.54) (p<.05). There were no significant differences (p>.05) of the bond strength mean between thirds. The use of the association between NaOCl+EDTA+PUI or saline to clean the post space ensured greater bond strength of FGP cemented with Relyx U-200™ in comparison to irrigation with CHX.